Pectic polysaccharides: Targeting gut microbiota in obesity and intestinal health. (1st July 2022) - Lee, Hye-Bin; Kim, Young-Soo; Park, Ho-Young
Abstract: The gut microbiome is a complex ecosystem of the host body that maintains a balance with its host. In this context, dysbiosis can lead to inflammatory response, immune dysregulation, and various metabolic disorders. Dietary polysaccharides mediate gut microbiota and its metabolites related to host health. In this review, we describe the structural characteristics of pectic polysaccharides and the functional correlation between their structure-specific characteristics and the modulatory activity of gut microbiota. We also discuss the health benefits of pectic polysaccharides on diet-induced obesity and intestinal health based on their source and structure. By regulating gut microbiota, pectic polysaccharides exert a wide range of biological effects, including the inhibition of obesity, fatty liver disease, and inflammation, and the increase in gut barrier function and immune-enhancing activity. This review expected to serve as a valuable resource to further clarity the relationship between pectic polysaccharides and gut microbiota. Graphical abstract: Unlabelled Image